2012
DOI: 10.3892/ol.2012.1020
|View full text |Cite
|
Sign up to set email alerts
|

Rapidly evolving asymptomatic eosinophilia in a patient with lung adenocarcinoma causes cognitive disturbance and respiratory insufficiency: Case report

Abstract: Paraneoplastic eosinophilia is an unusual manifestation that usually remains asymptomatic. In this report, we presented the case of an 82-year-old patient with poorly differentiated lung adenocarcinoma and asymptomatic eosinophilia. The patient’s condition worsened rapidly over a week, with episodes of cognitive disturbance, shortness of breath and acute kidney dysfunction. These symptoms were associated with a 4-fold increase in circulating eosinophil counts. The poor condition hindered further anticancer tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Unlike primary eosinophilia, which responds to steroids, paraneoplastic eosinophilia can be resistant. Sometimes a combination of steroids and hydroxyurea can increase the response rate [ 6 ]. However, the cornerstone of management includes treating the malignancy by either chemotherapy or surgery [ 4 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike primary eosinophilia, which responds to steroids, paraneoplastic eosinophilia can be resistant. Sometimes a combination of steroids and hydroxyurea can increase the response rate [ 6 ]. However, the cornerstone of management includes treating the malignancy by either chemotherapy or surgery [ 4 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, solid tumors can cause eosinophilia in some cases [ 5 ]. The incidence of eosinophilia in malignant tumors is estimated to be approximately 1% [ 6 ]. Eosinophilia presentation can be silent and life-threatening.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism contributing to eosinophilia in malignant diseases has not yet been fully determined. It has been suggested that three cytokines, namely interleukin-3 (IL-3), interleukin-5 (IL-5), and granulocyte-macrophage colony-stimulating factor (GM-CSF), may act as a potential eosinophilopoietin polypeptide ( 6 , 13 , 15 , 24 , 25 , 29 , 35 , 50 , 51 , 76 , 82 , 83 ). Unfortunately, in our patient, neither the level of IL-5, IL-3, and GM-CSF in serum was determined nor immunohistochemical staining with indicated antibodies was performed.…”
Section: Discussionmentioning
confidence: 99%
“…Among the one hundred previously reported and analyzed by us cases of TABE, the death of 68 patients was reported ( 4 , 7 , 8 , 10 – 14 , 16 – 22 , 24 – 28 , 30 , 32 , 34 37 , 39 , 44 , 46 – 51 , 53 60 , 65 , 67 69 , 71 , 72 , 74 76 , 82 – 88 , 94 96 ). About 90% of the deaths occurred within one year after the diagnosis of paraneoplastic hypereosinophilia.…”
Section: Discussionmentioning
confidence: 99%
“…24 If treatment fails (eg, metastatic lung cancer refractory to chemotherapy), management of the HES with corticosteroids may improve the patient's quality of life. 28 The approach to drug allergy depends on the clinical presentation and the complexity of comorbidities and their treatment. Patients with severe, potentially life-threatening complications of HE, such as DRESS syndrome, cardiomyopathy, or pulmonary hypersensitivity, should be hospitalized for surveillance and treatment.…”
Section: Treatment Of Hypereosinophilic Syndromes Associated With a Kmentioning
confidence: 99%